Determinants of User Satisfaction with Service Quality as Mediator at the Central Unit of Library Services and Manuscripts Collections of the National Library of the Republic of Indonesia - Mindhar Winanti, Indah; Herawati, Aty (Siber Journal of Advanced Multidisciplinary, 2024)
According to Law no. 43 of 2007 Libraries are institutions that manage collections of written works, printed works and/or artistic works professionally with a good system to meet the educational, research, preservation, information and recreational needs of users. The National Library of the Republic of Indonesia is the national institution that implements this law. The aim of this research is to analyze user satisfaction at the National Library of the Republic of Indonesia at the Central Unit of Library Services and Manuscript Collections and analyze service quality as a mediator variable. The variables used as factors influencing user satisfaction in this research are facilities and information technology. The research was conducted by surveying 100 visiting users using convenience sampling techniques. Data analysis was carried out using path analysis. The results of the research are that there is an influence of facilities and information technology on service quality and service quality has an influence on user satisfaction.  Service quality is a mediating variable, meaning that user satisfaction is influenced by facilities both directly and indirectly through service quality and user satisfaction is influenced by information technology both directly and indirectly through service quality.